2006
DOI: 10.1598/jaal.50.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Manga Hype: Uncovering the Multimodality of Comic-Book Literacies

Abstract: The authors introduce manga to educators, inspired by the comics' explosive entry into U.S. popular culture. The word manga refers specifically to printed, Japanese‐style comics found in graphic‐novel format—not to be confused with anime (animated Japanese cartoons, including moving images on television, movies, video games). There are two strong reasons that warrant directing educators' attention toward manga. First, there has been a sharp rise in the comics' popularity, evident by record‐setting sales of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 15 publications
0
20
0
3
Order By: Relevance
“…S e p t e m b e r 2 0 1 0 comics, or manga-Japanese for "amusing drawings" (Schwartz & Rubinstein-Ávila, 2006)-digital movie composing (Brass, 2008;Ranker, 2008), graffiti (Vasudevan, 2006), online fanfiction (Black, 2005), cell phone advertising (Ajayi, 2009), illustrated stories (DeBruin-Parecki & Klein, 2003), and rap lyrics (McGinnis, 2007).…”
mentioning
confidence: 99%
“…S e p t e m b e r 2 0 1 0 comics, or manga-Japanese for "amusing drawings" (Schwartz & Rubinstein-Ávila, 2006)-digital movie composing (Brass, 2008;Ranker, 2008), graffiti (Vasudevan, 2006), online fanfiction (Black, 2005), cell phone advertising (Ajayi, 2009), illustrated stories (DeBruin-Parecki & Klein, 2003), and rap lyrics (McGinnis, 2007).…”
mentioning
confidence: 99%
“…Researchers (Jewitt, ; Schwartz & Rubinstein‐Ávila, ) have found that multimodal reading skills require the reader to engage with the particularities inherent in each mode and negotiate them simultaneously during the reading. Vasudevan, DeJaynes and Schmier () argued that by bringing into the classroom a variety of modes together in one text, teachers allow for the reading experience to change, opening up multiple ways of making meaning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As a researcher, I often encounter resistance from school stakeholders when I wish to engage them about graphic novel use in schools. Other researchers of graphic novels in education (e.g., Downey, ; Lapp, Wolsey, Fisher, & Frey, ; Schwartz & Rubinstein‐Ávila, ) have also acknowledged that the notion of using this format in the classroom is often met with skepticism by adult stakeholders in the education community. One of the most profound statements that I encountered came from a high school student I had interviewed about graphic novels: “These [graphic novels] aren't real reading.” This phrase has stuck with me since that interview and has made me wonder, Is graphic novel reading “real” reading?…”
mentioning
confidence: 99%
“…One of the most frequently mentioned benefits of using graphic novels in classrooms focuses on how the visual nature of these texts enhances comprehension. According to various researchers and practitioners, graphic novels can: aid readers with visualization and assist those readers who may have limited language proficiency (Lyga 2006); offer English Language Learners picture support and less text, as well as exposure to authentic and conversational discourse and 'nuances of the English language' (Thompson 2008, 18); promote language and literacy development (Gorman 2008;Schwarz 2006), including vocabulary development (Brenner 2006); develop critical thinking and comprehension skills (Carter 2007;Jacobs 2007;Lyga 2006;Schwarz 2006); teach readers about literary techniques, terms and elements (Bucher and Manning 2004;Carter 2007;Esquivel 2006); foster multiple literacy skills (Bucher and Manning 2004;Jacobs 2007;Lyga 2006;Schwarz 2006;Schwartz and Rubinstein-Avila 2006); provide opportunities for media literacy education (Carter 2007;Schwarz 2007); and scaffold writing instruction (Frey and Fisher 2004). By participating in the classroom-based research projects, the Grade 7 students had opportunities to develop their understanding and appreciation of picturebooks and graphic novels, to extend their comprehension, interpretive and creative skills as they discussed and responded to the literature, and to apply their learning by designing their own multimodal print texts.…”
mentioning
confidence: 99%